Analysis of Stock Portfolio Optimization in the Telecommunications Sector Using the Single Index Model - Irwan, Irwan; Abdy, Muhammad; Salsabila, Nurul Khofifah; Ahmar, Ansari Saleh (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to determine the optimal portfolio in the telecommunications sector listed on the Indonesia Stock Exchange based on the Jakarta Composite Index for the period January 2018–December 2020 using the Single Index Model. This type of research is an applied research. This type of research is applied research with secondary data obtained from the Indonesia Stock Exchange, Yahoo Finance, and Bank Indonesia. The number of samples taken is 5 stocks, namely TLKM, ISAT, EXCL, BTEL, and FREN. Based on the results of the analysis of the 5 stocks that are members of the JCI, the combination of 2 stocks that make up the optimal portfolio, namely ISAT and FREN, produces an expected return of 5.08% with a risk of 8.02%.